PERAN MOTIVASI DALAM MEMEDIASI PENGARUH MANAJEMEN PENGETAHUAN DAN KETERLIBATAN KERJA TERHADAP KINERJA PEGAWAI PEMERINTAH DAERAH KABUPATEN KONAWE SELATAN - Erwin Harahap; Murdjani Kamaluddin; Yusuf Yusuf (Pascasarjana Universitas Halu Oleo, 2023)
The purpose of this study was to examine and analyze The Role of Motivation in Mediating the Influence of Knowledge Management and Work Involvement on the Performance of Local Government Employees in South Konawe Regency. This type of research is explanatory research. The population of this research is the Officials of Local Government Organizations in the Regional Government of South Konawe Regency. The number of samples determined is 5 (five) Regional Government Organizations which were selected purposively. The research sample was taken using the census technique as many as 104 people. Collecting data using a questionnaire. The analytical tools used are descriptive analysis and SEM analysis with SmartPLS. The results showed that knowledge management directly had a positive and significant effect on employee performance, work involvement directly had a positive and significant effect on employee performance, motivation directly had a positive and significant effect on employee performance, knowledge management directly had a positive and significant effect on motivation, direct work involvement has a positive and significant effect on motivation, the effect of knowledge management on employee performance mediated by motivation has a positive and significant effect and the effect of work involvement on employee performance mediated by motivation has a positive but not significant effect